Search for charged Higgs bosons produced in vector boson fusion processes and decaying into vector boson pairs in proton-proton collisions at root s=13 TeV - (:unkn) unknown (SPRINGER, 2021)
A search for charged Higgs bosons produced in vector boson fusion processes and decaying into vector bosons, using proton-proton collisions at root s = 13 TeV at the LHC, is reported. The data sample corresponds to an integrated luminosity of 137 fb(-1) collected with the CMS detector. Events are selected by requiring two or three electrons or muons, moderate missing transverse momentum, and two jets with a large rapidity separation and a large dijet mass. No excess of events with respect to the standard model background predictions is observed. Model independent upper limits at 95% confidence level are reported on the product of the cross section and branching fraction for vector boson fusion production of charged Higgs bosons as a function of mass, from 200 to 3000 GeV. The results are interpreted in the context of the Georgi-Machacek model.
Keywords: BROKEN SYMMETRIES; NEUTRINO MASSES; GAUGE